Debunking the autocratic fallacy? Improving public goods delivery in Russia - Christian Fröhlich (Global Policy, 2023)
Russia's invasion of Ukraine has not only deeply challenged Russia's international standing but has also endangered its fragile domestic order. Data from the 2022 Berggruen Governance Index reveals that overall state capacity has been stagnating at a fairly low level since the beginning of the millennium, while democratic accountability has been declining steadily and profoundly. In contrast, the provision of public goods has strongly increased during the same period. This puts the assumption of the `autocratic fallacy'—the idea that sustained public goods delivery relies on democratic accountability in the long run—to the test. We argue that Russia's resource abundance allowed for the maintenance of a regime-supporting social contract with the population. However, the basis of that contract has changed significantly due to economic decline, fired by, among other factors, several waves of sanctions and the costs of war and will press the Russian government to find urgent solutions to sustain a high level of public goods provision under such unfavourable conditions.
Keywords: 320